SUFI EDUCATIONAL TENETS: Practical Encounters of Sufi Teachings and Educational Curricula - Subaidi, Subaidi (Teosofia: Indonesian Journal of Islamic Mysticism, 2016)
This research focused on Sufism of ‘Abdul Wahab al-Sya’rani and studied about the education components which covers: the aspects of purpose and teaching material, the aspects of teacher and students, the aspects of method and strategy in Sufism Education, as well as the relevance of Sufism education by as-Sya’rani with the development of character building. The objectives of this research are: a) To describe what the objectives and teaching materials in Sufism by as-Sya’rani are; b) To describe how the position of the teacher and students in Sufism education by as-Sya’rani is; c) To describe what the method in Sufism education by as-Sya’rani is; d) To describe how relevant the Sufism by as-Sya’rani with the development of character building is. This qualitative research uses hermeneutic approach. The analysis method used in this research is content analysis with the descriptive features.  The writer uses the hermeneutic approach because he efforts to describe the facts gained from text containing as-Sya’rani’s thoughts on Sufism education and performs the perception towards the sense of texts in effort to be possibly close to understand  the idea of as-Sya’rani’s Sufism education.